1991
DOI: 10.1093/ageing/20.6.417
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes of Serum Albumin in Elderly People Living in the Community

Abstract: The relationship of serum albumin at baseline to mortality, and longitudinal changes of serum albumin were investigated in a 10-year longitudinal study of 421 (197 men, 224 women) community residents aged 69-71. The 10-year survival rate was the lowest in the first quartile of serum albumin at baseline, followed by the second quartile, and third and fourth quartiles (p less than 0.05). In both sexes, 10-year survival curves did not differ between the group with diseases or disabilities at baseline or over time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 0 publications
1
42
3
Order By: Relevance
“…However, it is quite difficult to control completely for all potential confounding factors. In addition, in a 10-y longitudinal study, the rate of change in serum albumin did not differ between the groups with and without disease (12). The elderly live individually with various backgrounds, such as disease, physical activity or disability, health condition, and lifestyle.…”
Section: Discussionmentioning
confidence: 86%
“…However, it is quite difficult to control completely for all potential confounding factors. In addition, in a 10-y longitudinal study, the rate of change in serum albumin did not differ between the groups with and without disease (12). The elderly live individually with various backgrounds, such as disease, physical activity or disability, health condition, and lifestyle.…”
Section: Discussionmentioning
confidence: 86%
“…During that time, epidemiological methods and indicators such as the BMI, serum cholesterol, and serum albumin were developed and improved for their application in epidemiological studies of longevity, as well as that of non inflammatory diseases [17,18]. Both inter-and intra-population studies carried out for the Japanese elderly revealed that poor nutritional status was deleterious for longevity [2,3,5,6,10]. Shibata et al, compared food and nutrient intake in the individuals aged 65 years between Ōgimi Village, Okinawa Prefecture (well-known for the longevity of its residents), Nangai Village and Akita Prefecture (well-known for the extremely short life expectancy of its residents) [6].…”
Section: Discussionmentioning
confidence: 99%
“…Intra-population studies also showed that poor nutritional status, expressed in low BMI, low serum cholesterol and low serum albumin, as well as undesirable food intake, were risk factors for early death [5,6,8,19,20]. Poor nutritional status not only shortens life expectancy but it also deteriorates the functional capacity, cognitive function, and subjective well-being, categorized as quality of life in the elderly [2,21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past forty years, it has been developed as a residential area for commuters into the center of Tokyo, and for the retired. Koganei City was chosen by TMIG as the study area as one of the urban communities for search into healthy aging for more than fifteen years [2,3,4]. According to the population data of June 1991, the city had 103,672 persons in an area of 16km ~.…”
Section: Methodsmentioning
confidence: 99%